2019
DOI: 10.3354/dao03329
|View full text |Cite
|
Sign up to set email alerts
|

Modelling sea lice control by lumpfish on Atlantic salmon farms: interactions with mate limitation, temperature and treatment rules

Abstract: Atlantic salmon farming is one of the largest aquaculture sectors in the world. A major impact on farm economics, fish welfare and, potentially, nearby wild salmonid populations, is the sea louse ectoparasite Lepeophtheirus salmonis. Sea louse infestations are most often controlled through application of chemicals, but in most farming regions, sea lice have evolved resistance to the small set of available chemicals. Therefore, alternative treatment methodologies are becoming more widely used. One increasingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Another possible way of increasing the understanding of underlying causes of variation in the efficacy of lumpfish is to use biological modeling techniques to explore the interactive effect of lumpfish grazing and mate limitation on sea louse population dynamics under different environmental scenarios. McEwan et al [42] used an agent-based model (ABM) to simulate cleaner fish on a salmon farm to explore interactions between sea louse mating behavior, cleaner fish feeding rate, temperature, and external sea louse pressure. They found that sea louse mating has a substantial effect on sea louse infestations under a variety of environmental conditions.…”
Section: Small-scale Studiesmentioning
confidence: 99%
“…Another possible way of increasing the understanding of underlying causes of variation in the efficacy of lumpfish is to use biological modeling techniques to explore the interactive effect of lumpfish grazing and mate limitation on sea louse population dynamics under different environmental scenarios. McEwan et al [42] used an agent-based model (ABM) to simulate cleaner fish on a salmon farm to explore interactions between sea louse mating behavior, cleaner fish feeding rate, temperature, and external sea louse pressure. They found that sea louse mating has a substantial effect on sea louse infestations under a variety of environmental conditions.…”
Section: Small-scale Studiesmentioning
confidence: 99%
“…Temperature increases predator attack rate and reduce prey vulnerability (Pepi et al, 2018). Fluctuation in temperature severely affects reproductive behavior in animals due to mate limitation (McEwan et al, 2019). Thermal extremes effect growth in animals (Nishizaki & Carrington, 2015) and reduce offspring fitness in a cold-climate mainly in viviparous lizards (Cunningham et al, 2018).…”
Section: Behavioral Biomarkersmentioning
confidence: 99%
“…To manage sea louse infestation on salmon farms, farm operators use a variety of methods (Overton et al 2019), including, among others, parasiticides to kill the parasites, fallow periods between production cycles where farms are emptied of fish to interrupt the parasite's life cycle, mechanical delousing to remove sea lice from salmon, and cleaner fish that feed on sea lice attached on salmon. In many instances, neighboring salmon farms adopt integrated pest management (IPM) to limit the exchange of sea lice among farms (Brooks 2009) and reduce external infestation pressure (McEwan et al 2019). The success and maintenance of these interventions are contingent on an accurate and precise surveillance system.…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, neighboring salmon farms adopt integrated pest management (IPM) to limit the exchange of sea lice among farms (Brooks 2009) and reduce external infestation pressure (McEwan et al. 2019). The success and maintenance of these interventions are contingent on an accurate and precise surveillance system.…”
Section: Introductionmentioning
confidence: 99%